HUBUNGAN PENGETAHUAN TENTANG NUTRISI DENGAN KENAIKAN BERAT BADAN IBU HAMIL - Sri Martini; Wahyu Dewi Hapsari (Jurnal Profesi Bidan Indonesia, 2025)
Background: Pregnancy is a physiological period during which the fetus undergoes growth and development that requires additional nutrition. Pregnant women need a higher intake of nutrients than when they are not pregnant. This is because, in addition to meeting the mother's needs, nutrition is also important for fetal development (Permenkes RI, 2014). Weight gain in pregnant women can be used as an indicator to assess nutritional status because generally, all pregnant women experience similar weight increases. In Indonesia, the standard weight gain considered normal ranges from 9 to 12 kg. An optimal weight gain of 12.5 kg is the average representation used for normal pregnancies. Purpose: To determine the relationship between pregnant women's knowledge about maternal nutrition and weight gain in PMB Sri Lestari Ngembak village, Purwodadi subdistrict, Grobogan Regency. Method: The research method used is an analytical survey with a cross-sectional approach using the Kendall-Tau test. The sampling technique in this study used Total Sampling. Results: Based on the Kendall-Tau test data analysis with a p-value of 0.000 < 0.05, there is a relationship between pregnant women's knowledge and weight gain. Conclusion: There is a relationship between pregnant women's knowledge about maternal nutrition and weight gain in PMB Sri Lestari Ngembak village, Purwodadi subdistrict, Grobogan Regency.